PH-Assisted surface functionalization of selenium nanoparticles with curcumin to achieve enhanced cancer chemopreventive activity. Issue 76 (29th July 2016) - Yu, Shaoxuan; Wang, Yanru; Zhang, Wentao; Zhang, Yuhuan; Zhu, Wenxin; Liu, Yingnan; Zhang, Daohong; Wang, Jianlong
Abstract : A pH-assisted strategy is proposed for synthesizing curcumin-functionalized selenium nanoparticles (SeNPs@Cur), which well combine the advantages of SeNPs with those of Cur in cancer chemoprevention and overcome their limitations in application. Abstract : A facile pH-assisted method for synthesizing curcumin-functionalized selenium nanoparticles (SeNPs@Cur) with enhanced cancer chemopreventive activity is proposed in the present work. It is intriguing to observe that by controlling the pH value of the synthetic reaction system, water-insoluble Cur is successfully decorated on the surfaces of SeNPs@Cur through physical adsorption and the possible formation of Se–O bonds. Moreover, the as-prepared nanocomposites possess high drug conjugation efficiency (5.5%), good chemical stability and more uniform sizes and morphologies in comparison with bare SeNPs. Meanwhile, enhanced chemopreventive activity of SeNPs@Cur is demonstrated through the improvements of their free radical scavenging activities and the increases of their cytotoxicities against cancer cells. Cur surface decoration also increases cellular uptake of elemental Se and apoptosis in HepG2 cells. Studies on underlying mechanisms suggest that SeNPs@Cur-induced apoptosis is dependent on the activation of caspases and the overproduction of intracellular ROS. In conclusion, data herein indicate that the strategy to assemble antioxidant ligands on the surface of SeNPs is a potential way to design novel chemopreventive agents with better safety, tolerability and efficacy profiles.